An Investigation of The Effect of Extracellular Vesicles Isolated from Mouse Embryonic Fibroblasts on Wound Healing in an Experimental Diabetic Mouse Model - Bozkurt, Ahmet S.; Kaplan, Davut S.; Ceribasi, Ali O.; Orkmez, Mustafa; Canak, Asuman; Tarakcioglu, Mehmet (Acad Brasileira de Ciencias, 2022)
This study aimed to investigate the effects of Extracellular Vesicles (EV) secreted from mouse embryonic fibroblasts EV on wound healing of full-thickness skin defect in a diabetic mouse model. The study included both in vitro and in vivo experimental studies 82 mice. In the in vitro stage of the experimental study, hysterectomy was performed on two mice between the 13-14th days of pregnancy and then EV was isolated by cell culturing. VEGF, IL-6, and TNF-alpha biomarkers were examined in tissue homogenate. Moreover, tissue taken from wound area was also subjected to histopathologic scoring. EV augmented the effect of VEGF. Therefore promoted angiogenesis increases the transport of cells, essential oxygen and nutrients in the wound area. Extracellular vesicles isolated from mouse embryonic fibroblasts have been found to accelerate wound healing in diabetes. The findings obtained from this experimental study indicate that EV isolated from mouse embryonic fibroblasts accelerate the wound healing process in experimentally induced-diabetes in mice.
Keywords: mouse; embryonic; fibroblast; extracellular; vesicles